INDUCCIÓN DE LA FLORACIÓN EN CACAO (Theobroma cacao L.) MEDIANTE EL USO DE BIOESTIMULANTES A BASE DE L-α-AMINOÁCIDOS - Mejía Pinargote, Bryan Tadeo (2023)
The research was carried out on the "La Cueva del lobo" farm, located in the San Carlos parish, Quevedo canton, Los Ríos province, which has an area of 14 hectares destined for the production of cocoa (Theobroma cacao L.) CCN-51. The use of biostimulants based on L-α-amino acids was evaluated in the induction of flowering in this crop during the dry season of 2023. For this purpose, a completely randomized block design (CRBD) was used, with four treatments, three with biostimulants: T1= Equilibrium™ + Aminoquelant™ (0.5 + 1.0 L ha-1), T2= Equilibrium™ (1.0 Lha-1) and T3= Terrasorb Complex™ (1.0 Lha-1), applied on three occasions, and one without application of biostimulants (T4= Control), distributed in five replications.